2022
DOI: 10.3389/fpsyg.2022.937971
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing opportunities when individual engaged in intrapreneurship: The role of creative self-efficacy and support for innovation

Abstract: According to social cognitive theory, this study explored the relationship between intrapreneurship and opportunity recognition. We developed a moderated mediation model of creative self-efficacy as a mediator and support for innovation as a moderator linking intrapreneurship with opportunity recognition. Using a sample of 206 college students from Chinese universities, we found that intrapreneurship is positively related to opportunity recognition, and this relationship was mediated by creative self-efficacy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 148 publications
0
0
0
Order By: Relevance
“…Thus, confirming that MSE mediates the effect of OCB on IB. This finding is consistent with that of prior researchers (Uppathampracha & Liu, 2022;Hamzah et al 2022;and Liao et al 2022) that found that SE mediates several organizational relationships. Thus, when marketers perceive that they have a high level of SE, they are more likely to exhibit citizenship and innovative behaviors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, confirming that MSE mediates the effect of OCB on IB. This finding is consistent with that of prior researchers (Uppathampracha & Liu, 2022;Hamzah et al 2022;and Liao et al 2022) that found that SE mediates several organizational relationships. Thus, when marketers perceive that they have a high level of SE, they are more likely to exhibit citizenship and innovative behaviors.…”
Section: Discussionsupporting
confidence: 93%
“…SE mediated both connections in this context. Liao, Li, Zhang, and Yang (2022) investigated a moderated mediation model of creative SE as a mediator and support for innovation as a moderator linking intrapreneurship with opportunity recognition using a sample of 206 college students from Chinese universities. Results obtained from linear regression and hierarchical multiple regression analysis indicated that intrapreneurship is positively related to opportunity recognition, and this relationship was mediated by creative SE.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is when a self-leading individual works within an autonomy-supportive climate that feelings of meaning, competence and self-determination are experienced (Van Dorssen-Boog et al 2022 ). According to Liao et al ( 2022 ), self-leading individuals’ inclinations to be innovative, risk-takers and proactive are better leveraged in an autonomy-supportive climate.…”
Section: Introductionmentioning
confidence: 99%
“…It is when a self-leading individual works within an autonomy-supportive climate that feelings of meaning, competence and self-determination are experienced (Van Dorssen-Boog et al 2022). According to Liao et al (2022), self-leading individuals' inclinations to be innovative, risk-takers and proactive are better leveraged in an autonomy-supportive climate. Some authors have observed that self-leadership practices thrive in climates that support autonomy, thus boosting selfleadership skills and self-confidence (Nientied & Toska 2021;Ralph et al 2020).…”
Section: Introductionmentioning
confidence: 99%